STUDY OF SEA WATER QUALITY BASED ON PHYSICAL-CHEMICAL PARAMETERS IN THE WATERS OF THE MALAKA STRAIT - Djunaidi, Djunaidi; Widagdo, Aris; Kelana, Perdana Putra; Pramesthy, Tyas Dita; Arkham, Muhammad Nur; Haris, Rangga Bayu Kusuma; Hutapea, Roma Yuli F; EY, M. Habib (Politeknik Kelautan dan Perikanan Dumai, 2024)
It is feared that the high level of human activity in the coastal areas of Dumai City and Bengkalis City will have a polluting impact on water quality conditions. Therefore, to preserve coastal and marine functions, it is necessary to manage the quality and control of sea water pollution for present and future purposes as well as ecological balance. This research aims to determine the water quality of Dumai City and Bengkalis City, focusing on the concentration of several physical and chemical water parameters listed in the sea water quality standards for marine biota. Water quality sampling was carried out in May-August 2023 at 12 research stations, then the results were compared with sea water quality standards for marine biota. The research results show that the parameters that still comply with sea water quality standards for marine biota based on the Decree of the Minister of the Environment No. 51 of 2004 are temperatures in the range of 28.7-30.8˚C and an average value of 29.45˚C., pH ranged from 6.4–7.2, with an average value of 6.9 and dissolved oxygen (DO) ranged from 5.0 – 5.9 mg/l, with an average of 5.34 mg/l. Meanwhile, the parameters that do not comply with quality standards are low brightness ranging from 0.40 m-0.58 m with an average brightness of 0.47 m and salinity ranging between 22-28 ppt, with an average salinity of 24 ppt